Effect of Lanthanum Doping on the Structural, Morphological, and Optical Properties of Spray-Coated ZnO Thin Films - Manu Srivathsa; Bharathipura Venkataramana Rajendra (Engineering Proceedings)
In recent years, transparent conducting oxide semiconductor materials have found applications in both science and technology, especially in the areas of semiconductors, optoelectronics, and a wide range of energy efficiency devices. These TCO materials are the building blocks of various optoelectronic devices, such as transparent thin-film transistors, solar cells, and light-emitting diodes. This work concentrates on the structure, morphology, and optical properties of ZnO and Zn0.95La0.05O thin films at 673 K using a chemical spray technique. The polycrystalline nature and wurtzite structure of ZnO were confirmed by using XRD analysis with preferred growth along the (1 0 1) plane. The Zn0.95La0.05O deposits showed maximum crystallinity of 15.4 nm and a strain value of 2.4 × 10−3. The lattice constants increased for lanthanum-doped ZnO thin films due to the ionic radii mismatch of the doping material, which causes lattice expansion. Fibrous morphology was observed for ZnO, and a mixed structure of grains and fibers was observed for Zn0.95La0.05O films, which confirms the insertion of La3+ into the Zn2+ position. The Zn0.95La0.05O deposits showed transmittance above 80% due to the increased crystalline quality and a bandgap of 3.32 eV. The photoluminescence spectra showed peaks corresponding to e-h recombination, zinc defects (Zni and Ozn), and oxygen vacancy (Oi and Vo). The lanthanum-doped ZnO films showed increased band-edge emission and decreased defect-related peaks due to the increased crystalline quality. Hence, the doping of La3+ ions into a ZnO lattice enhances the crystalline quality and increases the transparency of the host ZnO matrix, which is suitable for optoelectric device applications.